Pelatihan Pengenalan Aplikasi Perkantoran (Typing Master dan Microsoft Word) Bagi Remaja Karang Taruna RW. 08 Kelurahan Cinere Kecamatan Cinere Depok Jawa Barat - Endang Supriyadi; Maya Sofiana; Rita Wahyuni (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
This training aims to improve the ten finger blind / blind system typing skill and be able to apply it to Microsoft Word application programs to be able to help quickly complete the administrative activities of the organization Karang Taruna RW.08 in the Cinere Sub-District Cinere Sub-District Depok West Java. By using the lecture method, practice and question and answer results in increased knowledge and understanding of youth youth related to material and practice as well as increased speed and accuracy in the process of making documents in Microsoft Word. From the results of the community service activities, it can be concluded that the knowledge and understanding of youth in youth has increased. Thus the skills of youth youth in utilizing the typing master application program and its application to Microsoft word also increased.